Magnetic resonance imaging study of safe needling depth and angulation for acupuncture at BL40. Issue 4 (August 2021) - Hou, Hai-Kun; Liu, Cun-Zhi; Lin, Lu-Lu
Objectives: The objectives of this study were to identify the mean safe needling depth and angle at BL40 between subjects, taking into account variables including sex and body mass index (BMI). Methods: One hundred and twenty-four participants who had undergone magnetic resonance imaging (MRI) examination of the knee region for clinical indications were included in this study. BL40 needling sites were localized by World Health Organization (WHO) standards and were measured by MRI. As much as 70% of the value of AN (from the needle insertion point to the popliteal artery) was considered to represent the safe depth, and angle alpha between the BL40 straight line and the AN line was regarded as the safe angle. Results: Overall, mean safe depth regardless of BMI and sex was 18.51 ± 3.56 mm (95% confidence interval (CI), 17.88%–19.14%). Mean safe depth was 17.24 ± 3.14 mm in the low and normal BMI group, 18.76 ± 2.90 mm in the overweight group, and 22.01 ± 3.71 mm in the obese group. Thirteen patients (10.5%) had internal deviation of angle alpha (95% CI, 5.6%–15.3%), while 111 patients (89.5%) had external deviation (95% CI, 84.7%–94.4%). The mean internal and external deviations of angle alpha were 8.78° ± 2.92° (95% CI, 7.01°–10.55°) and 9.75° ± 3.46° (95% CI, 9.10°–10.41°), respectively. Conclusion: We would suggest that, when using a straight needle insertion at BL40, it is safe to advance a 25-mm needle approximately 12.5 mm, and 17.5 mm should be safe for patients with BMI greater than 28 kg/m 2 . Practitioners should decrease the depth of penetration when treating patients of low body weight or height.